2020
DOI: 10.12688/f1000research.18713.1
|View full text |Cite
|
Sign up to set email alerts
|

Oral lichen planus: a novel staging and algorithmic approach and all that is essential to know

Abstract: Lichen planus (LP) is a chronic autoimmune disease. Oral lesions may occur in isolation or in combination with other affected muco-cutaneous sites. Oral LP (OLP) may present as one of the various manifestations of LP or may present as a disease sui generis with a broad range of severity. Despite this disease targeting the oral mucosa, its great impact on quality of life is underrated. In this article, we provide an updated review of the pathophysiology and epidemiology of OLP and offer guidance for its diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 62 publications
1
20
0
9
Order By: Relevance
“…A review on dental amalgam-associated oral lichenoid lesions (OLLs) and oral lichen planus (OLP) found that approximately one-third of patients experienced complete resolution, another one-third experienced partial resolution, and the remaining third had no resolution of OLP upon removal of the amalgam [ 8 ]. For patients with OLP, 89.2% of patients with positive patch tests and 78.9% of patients with negative patch tests experienced improvement with removal of the amalgam.…”
Section: Discussionmentioning
confidence: 99%
“…A review on dental amalgam-associated oral lichenoid lesions (OLLs) and oral lichen planus (OLP) found that approximately one-third of patients experienced complete resolution, another one-third experienced partial resolution, and the remaining third had no resolution of OLP upon removal of the amalgam [ 8 ]. For patients with OLP, 89.2% of patients with positive patch tests and 78.9% of patients with negative patch tests experienced improvement with removal of the amalgam.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment goals include reducing pain, healing ulcerative lesions, reducing the risk of cancer of the oral cavity, prolonging asymptomatic periods, and maintaining good oral hygiene and dental status [ 85 ].…”
Section: Lichen Planus (Lp)mentioning
confidence: 99%
“…In patients with OLP, establishing a bacterial plaque control program improved not only the frequency of gingival bleeding, but also the painful symptoms of the lesions and the general activity of the disease [ 50 , 85 ]. Figure 5 illustrates a treatment algorithm for the management of desquamative gingivitis due to lichen planus.…”
Section: Lichen Planus (Lp)mentioning
confidence: 99%
“…La etiología del LPO aún se desconoce y su patogenia no está del todo aclarada. Se sabe que corresponde a una respuesta inmune celular, que inducirían una respuesta inflamatoria crónica y apoptosis de queratinocitos de la mucosa oral (Shavit et al, 2020). Esta falta de conocimiento ha desencadenado múltiples controversias y el surgimiento de nuevas teorías que han intentado explicar su etiopatogenia (Aguirre-Urizar et al, 2020).…”
Section: Introductionunclassified